Pengaruh Strategi Pembelajaran Berdiferensiasi Produk Terhadap Kemampuan Menulis Teks Berita Pada Mata Pelajaran Bahasa Indoonesia Kelas VII SMP Islam Fathia Sukabumi Tahun Ajaran 2024/2025 - Yusuf, Maulana (PT. Alahyan Publisher Sukabumi, 2024)
Differentiated learning, also known as differentiated instruction, is a learning approach that embraces, supports, and recognizes the diversity of students in their learning processes. The implementation of this approach focuses on addressing the needs of individual students. Differentiated products, on the other hand, refer to the final outcomes of learning that demonstrate students' knowledge, skills, and understanding after completing a unit of study or even an entire chapter or semester. The aim of this research is to determine the impact of the differentiated product learning strategy on the ability to write news texts in the Indonesian language subject for seventh-grade students at SMP Islam Fathia Sukabumi. This study employs a quantitative experimental research method, utilizing a one-group design and T-Test Statistics for data analysis. Based on the pretest results, the average score was relatively low at 69.40, while the posttest results after the treatment showed a significant improvement with an average score of 89.96. The statistical testing using the T-test on the posttest scores indicated that the calculated t-value (9.20) was greater than the t-table value (2.096), with a significance level of 0.05 and a degree of freedom (df) of 23. Therefore, the calculated t-value was higher than the t-table value, leading to the acceptance of the alternative hypothesis (Ha). This indicates that the differentiated product learning strategy has a positive effect on students' ability to write news texts.